Pedagogical Challenges of Elementary School Teachers in Classroom Instruction - Tiarnita Maria Sarjani Br. Siregar; Desvi Putri Andriani Telambanua; Paulina Tambunan; Puji Kristian Gurning; Elmaria Situmeang; Paskah Valerius Sagala; Regina Naibaho (International Journal of Educational Research, 2026)
Pedagogical challenges faced by elementary school teachers remain a critical issue in classroom instruction. Teachers are expected to implement student-centered learning while addressing diverse student characteristics, increasing curriculum demands, limited instructional resources, and various classroom constraints. This study aims to understand and describe the pedagogical challenges experienced by elementary school teachers in classroom instruction through a qualitative library research approach. Data were collected from peer-reviewed journal articles published within the last five years and relevant academic books published within the last ten years. The selected literature was analyzed thematically to identify recurring patterns and key issues related to pedagogical practices. The findings indicate that major challenges include classroom management difficulties, the implementation of differentiated instruction, curriculum adaptation, technology integration, and limited opportunities for professional development. These challenges reveal a persistent gap between pedagogical theories and classroom realities. The study concludes that addressing pedagogical challenges requires not only teacher competence but also strong institutional support, flexible curriculum implementation, and continuous professional development.